Sistema Difuso Evolutivo para la Predicción del Nivel de Contaminación del Aire por Material Particulado: Caso Puente Aranda (Bogotá) - Riveros Varela, Carlos Alberto; Melgarejo Rey, Miguel Alberto; Riveros Varela, Andrea; Alvarado Nieto, Luz Deicy (Ingeniería, 2012)
This paper proposes the application of a Genetic Fuzzy System for prediction of air pollution levels in the short term. The method is validated for the specific case of Bogotá, Colombia, where the pollution level of particulate matter (PM10) for the next day is predicted from several variables such as temperature, speed and direction of wind, rain and level of PM10 of the current day. The results show that it is possible to obtain a satisfactory prediction of the level of contamination by PM10 using a Genetic Fuzzy System with a small number of rules, which would yield an easy human interpretation.